TEAM BUILDING AND COORDINATION FOR DESIGN -BUILD MULTIPLE PROJECTS - C.T, Ramanathan; Sambu Potty, Narayanan; M. Taharin, Radzif (Project Management Institute, 2007)

(untitled)
The construction industry, unlike other industries has unique problems in project management. When the organization undertakes multi projects involving multiple designers, contractors, subcontractors, construction managers, consultants and specialists the project management becomes more complex with many variables affecting the project execution. The key element of the smooth execution of a huge construction project is a suitable project organizational structure, with proper team building and effective coordination, which can improve the effective communication between different groups of project members. This work studies the vital importance of team building in a complex mix of human resources management, common sense, people skills, multi cultural team, technical understanding, and process facilitation. The tasks in creating a team that is best suited to multiple design and build projects in Sabah (East Malaysia) are identified. The case study highlights with examples the different team combinations giving certain type of strength to the project performance. The complexities in developing coordination and team building in an organizational structure are identified and methods to improve the skills in the project team and building effective coordination for successful project closure are recommended. The study also emphasizes the importance of the team’s work environment, structuring the work, training to maintain a qualified team and communication plan. Finally, it identifies several ways in developing proper coordination and team building in an organization involved in Multiple Design and Build projects located in Sabah. This is an attempt to add on valuable points to the Project Management Body of Knowledge (PMBOK) defined by the Project Management Institute.